2020
DOI: 10.1038/s41583-020-0336-9
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal vector coding in spatial cognition

Abstract: Several types of neurons involved in spatial navigation and memory encode the distance and direction (that is, the vector) between an agent and items in its environment. Such vectorial information provides a powerful basis for spatial cognition by representing the geometric relationships between the self and the external world. Here, we review the explicit encoding of vectorial information by neurons in and around the hippocampal formation, far from the sensory periphery. The parahippocampal, retrosplenial and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
119
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(128 citation statements)
references
References 112 publications
(188 reference statements)
9
119
0
Order By: Relevance
“…Consistent with this hypothesis, we observed that the magnitude of the advantage of STF over STD is proportional to the conductance of the Kv1 current (early spiking window: R 2 = 0.9, p = 2.88e-08; late-spiking window: R 2 = 0.82, p = 1.81e-06; Figure 4H&I). Overall, the synaptic dynamics of the inputs to LR neurons are thus better suited for temporal latency coding of thalamic directional inputs but a rate code for dorsal subicular distance-related inputs, such as those likely to be provided by bursty boundary vector cells in the dorsal subiculum (Bicanski and Burgess, 2020; Lever et al, 2009; Simonnet and Brecht, 2019; Stewart et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this hypothesis, we observed that the magnitude of the advantage of STF over STD is proportional to the conductance of the Kv1 current (early spiking window: R 2 = 0.9, p = 2.88e-08; late-spiking window: R 2 = 0.82, p = 1.81e-06; Figure 4H&I). Overall, the synaptic dynamics of the inputs to LR neurons are thus better suited for temporal latency coding of thalamic directional inputs but a rate code for dorsal subicular distance-related inputs, such as those likely to be provided by bursty boundary vector cells in the dorsal subiculum (Bicanski and Burgess, 2020; Lever et al, 2009; Simonnet and Brecht, 2019; Stewart et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Further work is needed to determine whether any particular subtype of layer 5 pyramidal neurons may exhibit substantial TC-evoked responses, but our results, reporting significantly larger responses to TC input by LR neurons, suggest LR cells are the predominant spatial information-encoding subtype within RSG. The dorsal subiculum, which serves to transmit allocentric spatial information, including axis cell and boundary vector signals (Lever et al, 2009; Derdikman, 2009; Olson et al, 2017; Simonnet and Brecht, 2019; Bicanski & Burgess, 2020), also precisely targets LR neurons via projections localized to layer 3 of RSG (Figure S3; Nitzan et al, 2020; Yamawaki et al, 2019a). These inputs overlap with LR cell bodies and basal dendrites and have been shown to evoke larger excitatory postsynaptic currents in superficial compared to layer 5 pyramidal neurons (Figure S3; Nitzan et al, 2020; Yamawaki et al, 2019a).…”
Section: Discussionmentioning
confidence: 99%
“…Proprioceptive feedback and sensorimotor integration may play a vital role in reshaping spatial selectivity of hippocampal and cortical neurons (Acharya et al, 2016; Aghajan et al, 2015; Ravassard et al, 2013). It may not come as a surprise that the spatio-visual map in visual cortex encoded both egocentric and allocentric spatial cues in parallel (Bicanski and Burgess, 2020; LaChance et al, 2019; Wang et al, 2020). How and whether hippocampal-entorhinal spatial signals interact with non-visual navigational signals in the visual cortex awaits for further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have begun to explore how different types of spatial information may be tracked by specific brain regions during navigation. Two important metrics for flexible navigation are vector-to-goal and path-to-goal (Bicanski and Burgess, 2020; Chadwick et al, 2015; Spiers and Barry, 2015). Using in situ learning experience and film simulation of Soho in London (UK), Howard et al (2014) identified neural correlates of path distance to goal in the right posterior hippocampus.…”
Section: Flexibility During Goal-directed Behaviourmentioning
confidence: 99%